Avaliação epigenética do gene BDNF e a relação com a insegurança alimentar e nutricional em usuários do SUS - Luz, Thaiany Marcelino (2023)
Fear or concern about providing nutritionally for oneself and one's family are inherent to the condition of food and nutritional insecurity (INSAN) experienced by a socially vulnerable portion of the population. INSAN can establish itself as a chronic stress factor, triggering changes in the epigenome of genes involved in the response to stress and neurobiological development. Recent studies have shown that brain-derived neurotrophic factor (BDNF), a gene involved in neurodevelopment, can undergo epigenetic changes, such as DNA methylation, altering its expression. However, there are few studies on the effect of INSAN associated with stress on methylation of the BDNF gene. The objective of this study was to analyze the relationship between INSAN and BDNF gene methylation levels in adults. To this end, a cross-sectional study was carried out, with 379 individuals aged between 20 and 59 years old treated by the SUS basic health care network in the city of Alegre – ES. Data collection was carried out using a socioeconomic, health and lifestyle assessment questionnaire, as well as anthropometric assessment and food and nutritional insecurity situation, using the Brazilian Food Insecurity Scale (EBIA). Blood was collected for genomic DNA extraction and subsequent methylation analysis by pyrosequencing. The prevalence of INSAN was 41.7% in the analyzed sample. According to Poisson regression, the higher prevalence of INSAN in the sample was explained by stress (IRR=1.49), depression (IRR=1.59), leisure activity (IRR=0.75), housing (IRR= 1.53), education (IRR=0.75), per capita income (IRR=0.70) and self-reported health (IRR=1.34). Generalized Linear Model analyzes demonstrated that food-secure individuals had higher methylation levels when compared to food-insecure individuals (β = 0.014; pvalue=0.027). These results demonstrate the importance of observing how an external psychosocial factor, which is related to a pertinent socioeconomic issue, can act and cause changes at a biological level in a vulnerable population.